The prevalence of radiographic trochlear dysplasia in patients with patellar fractures - Vanessa Morello; Matthieu Zingg; Philippe Tscholl (BMC Musculoskeletal Disorders)
Abstract Purpose Trochlear dysplasia is found in 3.2% (95% confidence interval (CI) 1.2–6.7) of the general population and linked to patellar instability and anterior cruciate ligament (ACL) injuries. The purpose of this study was to evaluate the prevalence of radiographic trochlear dysplasia in patients with patellar fractures. Secondary outcome was to evaluate the prevalence of trochlear dysplasia in different type of patellar fracture. Methods All consecutive 18-year-old or older patients treated in a level-1 trauma center for patellar fracture between 2003 and 2016 were retrospectively evaluated. Trochlear dysplasia was assessed according to Dejour’s classification on a strict lateral knee x-ray. Patellar fractures were analyzed on AP, lateral and axial knee x-rays and classified on pattern and displacement. Patellar dislocation at time of injury was recorded. Results Out of 482 patellar fractures, a strict lateral knee x-ray was found in 166 cases (50.6% women, mean age 56years +/-21, 51% right knee). Nineteen cases had trochlear dysplasia (11.5%, 95% CI 6.9–17.9): 10 high-grade trochlear dysplasia meaning type B, C and D (6.0%, 95% CI 2.4–9.7%); 15 without dislocation (9.3%, 95% CI 5.2–15.3). Patellar fracture distribution showed 17 transverse non-displaced (10.2%), 38 transverse displaced (22.9%), 15 avulsion (9%), 27 multifragmented non-displaced (16.3%), 56 multi-fragmented displaced (33.7%), 7 vertical (4.2%) and 6 osteochondral (3.6%) fractures. Four dislocations were recorded, all had osteochondral fractures and trochlear dysplasia. When considering patellar fractures with dislocation, the incidence of osteochondral lesions was significantly higher in patients with trochlear dysplasia (p < 0.001). This is not true for any other type of patellar fracture (p = 0.138). Conclusions This study suggests that there is a significant prevalence of trochlear dysplasia in patients with patellar fractures. This study also suggests that the pattern of patellar fracture is not influenced by the presence of trochlear dysplasia, except for osteochondral fractures associated with patello-femoral dislocations.